The Influence of Organizational Culture on Employee Performance Through Leadership as an Intervening Variable in the Contex of Dinas Pendidikan Kabupaten Pulau Taliabu - Kamdilia Andiningsih; Zahera Mega Utama (Journal of Center for Energy Policy and Human Resources Capacity Development, 2025)
The purpose of this study is to examine the relationship between the performance of employees and the culture of the organization in the Department of Education in the Pulau Taliabu Regency via the lens of leadership as a variable that intervenes. The study utilizes entire sampling, which means that each member of the population has an equal chance of being chosen for the sample. The study utilizes an explanatory approach and a quantitative strategy. Leadership has a favorable effect on the performance of employees, and organizational culture also has a positive effect on performance. The Sobel test demonstrated, as did other tests, that there is a high association between the performance of employees and the culture of an organization. In addition, leadership serves as a mediating function between the two. The significance of establishing an effective leadership style and developing a strong company culture in order to increase employee performance is highlighted by these studies. Leadership development programs are to be strengthened in order to optimize the beneficial effects of business culture on employee outcomes, according to the practical implications.